Optimal Delegation and Information Transmission under Limited Awareness - Sarah Auster; Nicola Pavoni (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We study the delegation problem between a principal and an agent, who not only has better information about the performance of the available actions but also has superior awareness of the set of actions that are actually feasible. The agent decides which of the available actions to reveal and which ones to hide. We provide conditions under which the agent finds it optimal to leave the principal unaware of relevant options. By doing so, the agent increases the principal's cost of distorting the agent's choices and thereby increases the principal's willingness to grant him higher information rents. We also consider communication between the principal and the agent after the contract is signed and the agent receives information. We show that limited awareness of actions improves communication in such signalling games: the principal makes a coarser inference from the recommendations of the privately informed agent and accepts a larger number of his proposals.
Keywords: D82; D83; D86; 330; Asymmetrische Information; Prinzipal-Agent-Theorie; Signalling; Spieltheorie